How Hotel Industry Cope up with the COVID-19: An SME Perspective - Muhammad Nawaz Tunio; Lenny Yusrini; Zubair A. Shah; Naveeda Katper; Mushtaque Ali Jariko (ETIKONOMI, 2021)
This study aims to determine the plans and strategies adopted by the hotel industry during the COVID-19 crisis. In order to conduct this study, a qualitative research methodology was used where semi-structured interviews were conducted from three countries: Austria, Pakistan, and Indonesia. Interviews were conducted online with the help of applications such as Skype, WhatsApp, and Zoom. A thematic analysis was conducted in which codes, categories, and final themes were generated. The final themes are the study's findings, which are strategies for employees, strategies for customers, strategies for SME hotels, and strategies for the staff. Strategies for employees indicate the planning and programs of the SME Hotels. The study's findings show that strategies adopted by the hotel industries vary from country to country while depending on the contextual factors and role of the government. Most Small and Medium Enterprises (SMEs) hotels in developing countries are less familiar with how to react and survive in the conditions of the crises. Thus, this study can benefit the different stakeholders in the developed and developing countries for adopting strategies and maintain their business during the crises of the COVID-19.JEL Classification: B17, B27, F30, L83How to Cite:Tunio, M. N., Yusrini, L., Shah, Z. A., Katper, N., & Jariko, M. A. (2021). How Hotel Industry Cope Up With The Covid-19: An SME Perspective. Etikonomi, 20(2), 213 – xx. https://doi.org/10.15408/etk.v20i2.19172.